Bibliometric Mapping of Islamic Letter of Credit using VOSviewer - Siti Fatimah Azzahro (Journal of Islamic Economics Literatures, 2022)
This study aims to determine research trends regarding previous Islamic letters of credit, assess research collaboration relationships, and identify future research directions. Using 42 articles published between 2013-2020 on Islamic Letter of Credit. Using qualitative and quantitative approaches, namely Bibliometric and Systematic Literature Review (SLR) methods. This research uses Vos Viewers software. It is known that the three sub-themes that dominate research related to Islamic Letter of Credit are: Islamic Banking and Letter of Credit, Bank Regulation, and Business Financing. This study implies that there is still little research on Islamic Letters of Credit. It is hoped that Islamic Letters of Credit literature can adjust or find new methods that are suitable and accurate.